Prawa kobiet i mężczyzn w Korei Południowej : analiza porównawcza praw kobiet w Korei Południowej i w Polsce - Oleksiuk, Marlena (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
South Korea is very homogenous country, where their inhabitants are very proud of their national heritage. So, progress of social changes in this country is much slower than economic development. The doctrine of Confucianism dominates in the country with all its restrictive rules. The rules are visible in interpersonal relationship, especially in national hierarchy. Such an attitude to life has been teaching since Joseon Dynasty, which adapted Chinese confusion version for itself needs. Women rights in South Korea still are very restrictive. In 1948 women obtained equal rights for education, science and public life. Along with the increasing number of women in the labour market, in 1987 The Act of Equality in Employment was established to counteract discrimination against women at work. Unfortunately, the law designed to ensure the equality of both sexes in most cases are not respected. On average women earn 37% less than men, putting Korea next to Nigeria. Moreover, women often have to choose between a career and starting a family, because wives, in particular, mothers are badly perceived by employers and usually can no longer go back to work. It has an impact on increasing the low fertility rate in South Korea. In Korea there are also stereotypes reducing the role of women in development and ideas advocating that women always depends on the man. In 2016 took place absurd case, when a voice actress Kim Chae-yeon (kor. 김자연) was released from the company producing games for posting a photo in her T-shirt with inscription: Girls do not need a Prince. The company released a statement, that the decision was made after receiving multiple complaints from fans of the games. According to the report of the World Economic Forum, in the Korean Parliament we find only 49 deputies, while the number of men in 251. Despite the fact that Korea increasingly turns toward the American lifestyle, is still one of the most sexist societies among the countries of the first world. In 2016 South Korea held 116 place on 144 in the ranking of gender equality in the world. The country, despite the high level of civilization development of society still struggles with the problem of misogyny. Many women are still treated as second class citizens. They suffer because of domestic violence, are particularly vulnerable to crime, are often discriminated. Patriarchal image of society, family or relationship is still supported and developed by public media
Keywords: women’s rights; South Korea; equality